Developing interactive multimedia on the thematic-integrative learning for Grade IV students under the sub-theme my food is health and nutritious - Tri Yuliansyah Bintaro (Jurnal Prima Edukasia, 2017)
This study aimed at generative a proper and effective Adobe Flash Interactive Multimedia for Grade IB Students under the sub-theme “My Food is Healthy and Nutritious” in SD Negeri Glagah Yogyakarta. This research and development study referred to the stages that had been developed by Borg Gall. The development design was put into four stages, namely: (a) exploration; (b) product development; (c) product testing and revision; and (d) implementation. The subjects of preliminary field testing consisted of 15 Grade IV students in SD Negeri Glagah. Then, the subjects of expanded field experiment consisted of 30 Grade IV students in the experimental group and 29 Grade IV students in the control group; all of these students came from SD Negeri Glagah. The data were gathered using the interview guideline, the interactive multimedia product evaluation sheet, and the test items. The data that had been gathered were analyzed using the independent sample t-test with rate of significance 0.05. The results of this study have generated the interactive multimedia that according to the material experts and the media experts belong to the “Very Good” category. However, there have been differences in the pre-test results and the post-test results between the experimental group and the control group after both groups were exposed to the interactive multimedia with p 0.05. These differences imply effectiveness improvement with p = 0.005.